PENERAPAN MODEL PEMBELAJARAN TREFFINGER UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS V SDN 47 PEKANBARU - Putri, Shinta Amanda; Syahrilfuddin, Syahrilfuddin; N, Lazim (Jurusan Ilmu Pendidikan Fakultas Keguruan dan Ilmu Pendidikan Universitas Riau, 2019)
The background of this study is caused by fifth grade student have low learning out come in SDN 47 Pekanbaru.The standard score in school is 70 from 41 students,only 20 students has reached the standard score with percentage 48,78% and there are 21 students didn't reached standard score yet,with percentage 51,21% and average score is 60,24. the aimof this research is for increase learning outcome mathematics of fifth grade students SDN 47 Pekanbaru by implemertation of treffinger learning model.The result showed that the average score of 60,24 increase in cycle Iasi 27,53% to 76,82. In cycle II the average student also experienced an increase of 42.30% to 85.73. Teacher activity at the first meeting of cycle I the percentage is 65% with Enough category. The second meeting increased to 75% with good category. At the first meeting of the second cycle of teacher activity increased to 90% with good category. At the second meeting it increased to 95% with very good category. Student activity at first meeting of cycle I the percentage is 60% with enough category. The second meeting increased to 75% with good category. At the first meeting of cycle II student activity increased to 85% with good category. At the second meeting it increased to 95% with very good category.